The Tree Species of the Tropical Evergreen Ghat Forests of Kanara (Bombay) and their Rate of Growth - Mathauda, G. S. (Indian Forester, 1953)
Four permanent linear tree increment plots, 1 chain wide and 27.5 to 67 chains in length, were laid out in 1939 in the Eastern and Western Kanara Forest Divisions of Bombay in order to facilitate the identification of the complex tree flora of the local tropical wet evergreen forests and to determine the rate of growth of individual tree species. The information collected on these plots, during the period 1939 to 1949, forms the basis of this short note. Out of a total of 4002 stems, 4 inches and over in b.h. diameter, 3981 have been identified. The identified stems belong to 131 different species. The number of species represented in individual plots varies from 56 to 76 and their proportion from o.1 to 17.9 per cent. The number of natural orders varies from 26 to 32, the contribution of even the most frequent natural order being only 25.1%. The top canopy itself may be composed of 26 to 60 species, the commonest species being no more than 25.9% of the total. A detailed statement showing the number of stems for each species, in the different plots, by 4-inch diameter and 3 canopy classes is appended. Habits of some of the species with regard to their occurrence have been examined. Whereas a few out of these occur throughout the altitudinal range of nearly 1,500 feet, others show preference for the higher or lower elevations. Again, some species are scattered all over the plots in the form of single trees or very small groups, while others are found in isolated groups of varying sizes. It has been shown that, in each of these plots, and in the hypothetical crop represented by their averages, the numbers of trees in successive diameter classes form a geometric series, thereby proving that the law of de Liocourt with respect to balanced uneven-aged diameter distributions applies to the virgin tropical evergreen forests also. The exponential equations for the 5 above distributions have been worked out. Mortality figures for each of the plots during the ten-year period are given. These can serve as a basis for determining the gross yield. The data examined indicate that the law of de Liocourt is applicable also to the normal mortality in these forests. Based on the 3 quinquennial measurements which the plots have so far received, the average rates of growth of 19 most frequently occurring species have been determined and presented in tabular form.